2013
DOI: 10.1039/c3mt00163f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient preparation and metal specificity of the regulatory protein TroR from the human pathogen Treponema pallidum

Abstract: TroR is a putative metal-dependent regulatory protein that has been linked to the virulence of the human pathogen Treponema pallidum. It shares high homology with the well-known iron-dependent regulatory protein DtxR from Corynebacterium diphtheriae, as well as the manganese-dependent MntR from Bacillus subtilis. However, it has been uncertain whether manganese or zinc is the natural cofactor of TroR to date. Herein, we established an efficient method named "double-fusion tagging" to obtain soluble TroR for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…For example, the binding of Mn 2+ to the TroR enzyme was also reported as an entropy-driven process. 25 The fitting of the experimental data revealed the binding stoichiometry of Mn 2+ /enzyme (wt or C139S) in the range of 5-6, which is in agreement with the HR-ICP-MS results. The enzymes studied here had a His-tag (hexa histidine-tag) for purification reasons, and the His-tag is well known to bind not only Ni 2+ cations, but other cations as well.…”
Section: Importance Of the Conserved Cys Residues For Enzyme Activitysupporting
confidence: 85%
“…For example, the binding of Mn 2+ to the TroR enzyme was also reported as an entropy-driven process. 25 The fitting of the experimental data revealed the binding stoichiometry of Mn 2+ /enzyme (wt or C139S) in the range of 5-6, which is in agreement with the HR-ICP-MS results. The enzymes studied here had a His-tag (hexa histidine-tag) for purification reasons, and the His-tag is well known to bind not only Ni 2+ cations, but other cations as well.…”
Section: Importance Of the Conserved Cys Residues For Enzyme Activitysupporting
confidence: 85%
“…T. pallidum troABCD was shown to be negatively regulated by a zincresponsive transcriptional regulator, TroR, a DtxR-like repressor (29). However, a later study showed that T. pallidum TroR is a manganese-dependent rather than a zinc-dependent regulator (31). Unlike many other bacteria, T. pallidum does not contain Zur, and the regulator of T. pallidum znuABC has not been reported.…”
mentioning
confidence: 96%
“…The ferric uptake regulator Fur and zinc uptake regulator Zur constitute the majority of the Fur family metalloregulators, being widely distributed in diverse lineages of Bacteria but not Archaea, whereas the manganese-and nickel-specific regulators Mur and Nur were found in only some bacterial lineages (9,10). Manganese-responsive DtxR family regulators were studied in many bacteria, including MntR in Escherichia coli (11), Bacillus subtilis (12), Staphylococcus aureus (13), Corynebacterium diphtheria (14), and C. glutamicum (15,16), ScaR in Streptococcus gordonii (17), and TroR in Treponema pallidum (18), where they mostly control genes for manganese uptake transporters. In contrast, iron-responsive TFs from the DtxR family were found only in Actinobacteria and include two experimentally studied TFs, the diphtheria toxin repressor DtxR in Corynebacterium diphtheriae (19) and the iron-dependent regulator IdeR in Mycobacterium tuberculosis (20,21), which control large networks of genes involved in iron homeostasis and other cellular functions, such as the toxin gene in C. diphtheriae.…”
mentioning
confidence: 99%